Legal Studies on EU Policies: Why Labour Migration Status as a Binary - Nguyen Thuy Anh (Universitas Lampung, 2023)
In the framework of the post-Covid-19 pandemic, Europe is facing two problems in terms of migrant workers: a shortage of agricultural production workers in some countries and the